Integrated Waste Management in the Circular Economy Era: Insights from Research and Practice - Charisios Achillas; Christos Vlachokostas (Energies)
This Special Issue on integrated waste management explores innovative approaches and multifaceted strategies aimed at addressing the critical challenges facing modern waste management systems. The featured eight original research articles cover diverse topics, including sewage sludge valorization, municipal waste biodrying, recyclables collection optimization, biomass-to-energy policies, and the management of compostable packaging waste. Technological advancements, such as AI-driven waste sorting and route optimization algorithms, are highlighted alongside policy frameworks supporting circular economy principles. The studies also address barriers to implementation, including public awareness gaps, technological disparities, and financial constraints, while emphasizing the importance of stakeholder collaboration across governments, industries, and communities. Additionally, environmental risks associated with waste management practices, such as nanoparticle contamination and leachate emissions from ashes, are critically analyzed. This Special Issue provides a holistic perspective on waste management, combining technical innovations, environmental stewardship, and policy integration. The insights of the works published in this Special Issue aim to guide researchers, policy-makers, and practitioners toward building resilient, sustainable, and resource-efficient waste management systems in alignment with global sustainability goals.